2013
DOI: 10.1002/smll.201301366
|View full text |Cite
|
Sign up to set email alerts
|

One‐Step Formation of a Single Atomic‐Layer Transistor by the Selective Fluorination of a Graphene Film

Abstract: In this study, the scalable and one-step fabrication of single atomic-layer transistors is demonstrated by the selective fluorination of graphene using a low-damage CF4 plasma treatment, where the generated F-radicals preferentially fluorinated the graphene at low temperature (<200 °C) while defect formation was suppressed by screening out the effect of ion damage. The chemical structure of the C-F bonds is well correlated with their optical and electrical properties in fluorinated graphene, as determined by X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 21 publications
0
42
0
Order By: Relevance
“…Specifically, a polymer nanowire mask was used to selectively expose graphene to ambient XeF 2 gas ambient27. Recently, we have successfully fabricated a unique semi-metal/semiconductor/insulator heterojunction structure directly using a single graphene sheet via a selective fluorination process28. This technique can potentially be used for the integration of electronics at the single atomic layer scale.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, a polymer nanowire mask was used to selectively expose graphene to ambient XeF 2 gas ambient27. Recently, we have successfully fabricated a unique semi-metal/semiconductor/insulator heterojunction structure directly using a single graphene sheet via a selective fluorination process28. This technique can potentially be used for the integration of electronics at the single atomic layer scale.…”
mentioning
confidence: 99%
“…Herein, we present a novel graphene-based field effect transistor architecture in which fluorographene is introduced as the gate dielectric material. The CVD-grown graphene was fluorinated using a low-damaged CF 4 plasma treatment, which allows for its integration with IC fabrication to achieve large-area processing28. During this process, a filter is inserted between the CF 4 plasma and graphene sheet to reduce damage caused by high energy radicals and UV photons.…”
mentioning
confidence: 99%
“…The absence of shift leads to two possible conclusions: firstly that FGr is transparent at these wavelength, or that there is absorption in FGr but limited charge transfer between graphene and FGr. The former can be eliminated as absorption measurements of FGr with a similar fluorine content (19%) demonstrated a band gap of 2.48 eV, [15] well below the photon energy used here (3.1 eV).…”
Section: Optoelectronic Characterizationmentioning
confidence: 73%
“…Furthermore, demonstration of nanoscale patterning of fluorinated graphene by electron beam irradiation allows for further miniaturization of optoelectronic devices. [12] The optical properties of fluorinated graphene have been widely investigated both experimentally, using absorption and photoluminescence spectroscopy, [13][14][15] and theoretically. [16] These works all indicate that the band gap of FGr can be tuned from the ultraviolet to near-infrared by controlling the degree of fluorination.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been shown that F-functionalized graphene can be prepared using F-based plasma treatments to provide a highly stable covalent bond of C2F [50 -52]. Furthermore, to achieve local fluorination, a patterned buffer layer during the CF 4 plasma treatment has been successfully demonstrated [53].…”
Section: New Routes To Patterning Fecl 3 -Functionalized Graphene Formentioning
confidence: 99%